Environment, taxonomy and morphology constrain insect thermal physiology along tropical mountains. (25th May 2022) - Bota‐Sierra, Cornelio A.; García‐Robledo, Carlos; Escobar, Federico; Novelo‐Gutiérrez, Rodolfo; Londoño, Gustavo A.
Abstract: Tropical mountains display limited variation in monthly temperatures, but high spatial climatic variability. It is assumed this stability promotes ecological and physiological adaptations to local temperatures, which may preclude dispersal up or downslope. Determining how environmental, taxonomic and morphological factors affect thermal limits is fundamental to understand biotic responses to global warming. We selected 54 species of dragonflies and damselflies (Order Odonata) distributed from 300 to 2, 550 m along one of the most biodiverse regions on the planet, the Tatamá elevational gradient in the Andean‐Choco region transition. We estimated for 846 individuals three thermal tolerance parameters: CTmax, the highest temperature preceding the loss of motor control, T vol, the temperature at which individuals avoid heat, and CTmin, the minimum temperature required for wing movement. For each thermal tolerance parameter, we evaluated associations between physiological and behavioural responses, species elevational distribution and specialization to forests or open areas. We also evaluated the effect of autecological characteristics such as body mass, sex and taxonomy on temperature regulation. Temperatures prevalent at different elevations and habitats are associated with odonate upper thermal limits. However, tolerance to low temperatures is not associated with habitat use or elevation. Forest species display lower thermal tolerances. Small species are more tolerant to high temperatures than larger species. Dragonflies are more tolerant to high temperatures than damselflies with similar body mass. Females are more tolerant to high temperatures than males. Our results highlight the importance of considering differences in morphology, life history and behaviour when comparing thermal tolerances of organisms along elevational gradients. Only by incorporating such factors, it would be possible to generate accurate predictions on the impact of climate change on tropical organisms. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.